ANALISIS KURANGNYA KONSENTRASI PEMBELAJARAN AKIDAH AKHLAQ DI KELAS IV MIN 10 BANDAR LAMPUNG - Teguh Yunianto; Lutfiyyah Hanifah; Yuli Setianingsih; Dina Shofiyyah; Yuniar Rizki Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This is to deeply identify the fundamental factors that cause the lack of concentration, as well as formulate alternative learning methods that are more effective and interactive.The research method used is a qualitative descriptive approach. Data collection techniques involve participatory observation, structured interviews with teachers and students, and documentation studies.The research results identify that the dominant factors causing low concentration include: lack of variation in teaching strategies, minimal use of attractive, interactive learning media, and high frequency of lecture method application.As a practical implication, this research recommends a transition from the lecture method to a more student-centered learning approach, such as group discussions or the integration of visual media, to optimize student engagement and concentration in the Akida learning process.